Biofortification of soilless culture using beneficial microbes and compost for cultivation of chilli (Capsicum annuum) under deficit fertigation - Karim, Mohd Fauzihan (2012)
Water and fertilizer are crucial in determining plant growth and production. The use of beneficial microbes is one of several approaches that have potential to be an alternative as plant growth promoters even at under water limited conditions. In the present study, attempts were made to enhance the growth of chilli using Azospirillum brasilense Sp7, Bacilluss sphaericus UPMB10, Rhizobium sp. UPMR31 and mycorrhizal fungi inoculated in the root rhizosphere. Preliminary study were carried out using Azospirillum brasilense Sp7, Bacilluss sphaericus UPMB10, Rhizobium sp. UPMR31 as plant enhancer to evaluate the efficacy of the microbes under serial degrees of deficit fertigation. The results showed increase in yield and plant biomass in inoculated plants compared to non-inoculated plants when subjected to 80 %. 60 %, 40 % and 20 % deficit fertigation. The inoculation effect also increased with amendment of empty fruit bunch into growing media of coconut dust fiber. Generally with decreasing level of water, greater losses in yield were observed. However, in the second experiment, inoculation of Sp7, UPMR31 and mycorrhiza reduced the extent of growth suppression and the bacterial treated plants accumulated more fruit yield and plant dry weight than the untreated plants especially when compost was added. Besides that, microbial inoculation was capable to maintain the physiological status in plants such as photosynthesis and relative water content. In the 3rd experiment, Azospirillum brasiliense Sp7 had increased the growth rate of plants and it could be seen in different stages of growth. Inoculation reduced the antioxidant enzymes activities in inoculated plants but increased the proline content. At the end of the study, it was concluded PGPR is able to increase plant’s tolerance to deficit fertigation stress especially with the presence of empty fruit bunch compost as the strategy to increase the efficiency of fertigation management.